Management information systems : managing the digital firm - Laudon, Kenneth C.; Laudon, Jane P.; Raj,Sahil (Noida : Pearson, 2022)
"Management Information Systems, 17th edition has been thoroughly updated to cover the latest industry and technology changes that impact the course"--
PART 1. Organizations, Management, and the Networked Enterprise -- Information Systems in Global Business Today -- Global E business and Collaboration -- Information Systems, Organizations, and Strategy -- Ethical and Social Issues in Information Systems -- PART 2. Information Technology Infrastructure -- IT Infrastructure and Emerging Technologies -- Foundations of Business Intelligence: Databases and Information Management -- Telecommunications, the Internet, and Wireless Technology -- Securing Information Systems -- PART 3. Key System Applications for the Digital Age -- Achieving Operational Excellence and Customer Intimacy: Enterprise Applications -- E commerce: Digital Markets, Digital Goods -- Managing Knowledge and Artificial Intelligence -- Enhancing Decision Making -- PART 4. Building and Managing Systems -- Building Information Systems -- Managing Projects -- Managing Global Systems.
Includes bibliographical references and index.
Keywords: Management information systems; Management information systems